Kazan scientific school of journalism: Definition of paradigmatic boundaries - D.V. Tumanov; A.S. Bik-Bulatov; S.K. Shayhitdinova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper summarizes the preliminary results, outlines the milestones and the prospects for the formation and development of the Kazan school of journalism. The authors of the paper represent three generations of researchers, who are the representatives of the teaching staff of the Department of Journalism of the Kazan Federal University, where teaching journalism at the Kazan University was initiated 55 years ago, thereby leading to the development of a journalism science in the Volga region. Having appealed to the discussions on the concept of “scientific school”, we formulated the criteria for its separation. An overview of Russian schools of journalism has been performed. A tribute has been paid to the founders of the Kazan school and its followers. The main methodological approaches have been described. Based on the obtained results, the following paradigmatic principles of the Kazan school have been formulated: 1) the principle of humanism, which determines the priority of the “human situation” over technologies; 2) the principle of personality prevalence (a personalized approach to the historiography of journalism); 3) the principle of dialogic journalism, which ensures the unity of different models, discursive practices of journalism, and media processes in general; 4) the principle of media culture, which determines the coherent connectivity of situationality and processuality of the object of research, its genesis and actual existence, metaphysics and pragmatics.